Anti‐Icing: Delaying Ice and Frost Formation Using Phase‐Switching Liquids (Adv. Mater. 17/2019). Issue 17 (18th April 2019) - Chatterjee, Rukmava; Beysens, Daniel; Anand, Sushant
Abstract : As described by Sushant Anand and co‐workers in article number 1807812, water droplets condensing on solidified phase‐switching liquids (PSLs) chilled to frigid temperatures "dance" on the surface, fueled by melting of the surface induced by the intermittent condensation heat flux; this eventually delays surface icing/frosting for prolonged periods of time.